PERTANGGUNGJAWABAN PIDANA KORUPSI BARANG MILIK DAERAH BERUPA TANAH - Syaifullah; Nining; Slamet Riyady (Collegium Studiosum Journal, 2026)
Corruption constitutes an extraordinary crime that has serious implications for both national and regional development, as it causes substantial financial losses to the State and hinders public welfare. One of the most prevalent forms of corruption is the abuse of authority by public officials for the purpose of enriching themselves, other individuals, or corporations. This study aims to examine the criminal liability of perpetrators involved in the corruption of Regional Government Property in the form of the Toro Lema land assets located in Labuan Bajo Village, Komodo District, West Manggarai Regency, as adjudicated in Decision Number 25/Pid.Sus-TPK/2021/PT Kpg. The research employs a normative juridical method using statutory and case approaches through an analysis of relevant legislation and judicial decisions. The findings indicate that the defendant’s conduct fulfilled the constituent elements of corruption as stipulated in Article 2(1) and Article 3 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, as amended by Law Number 20 of 2001. The court correctly applied the relevant legal provisions by taking into account the abuse of official authority that resulted in substantial financial losses to the State, thereby ensuring legal certainty while reinforcing Indonesia’s commitment to combating corruption.